COMPETITIVE MECHANISMS FOR FINANCING INNOVATION AND INVESTMENT PROJECTS - N. I. Komkov; A. A. Lazarev; K. I. Lugovtsev; N. V. Yakunina (Модернизация, инновация, развитие, 2016)
The article deals with the organizational and methodological basis for the formation of competitive technologies and innovative fi nancing mechanisms and investment projects. The stages of development of methods and algorithms for the selection of projects as more is learned about the processes of research and development. A classifi cation of possible technologies and tools for project selection, and shows the features of the technologies used existing investment structures (foundations and companies).